Resuspension and settlement characteristics of lake sediments amended by phosphorus inactivating materials: Implications for environmental remediation. (15th January 2022) - Wang, Changhui; Wei, Zhao; Zhao, Yuanyuan; Bai, Leilei; Jiang, Helong; Xu, Huacheng; Xu, Youze
Abstract: The classical lake internal phosphorus (P) pollution control using P-inactivating materials is typically carried out by reducing the release of soluble P from sediments to overlying water; however, particulate P loading through sediment resuspension could also cause internal P pollution for algae breeding. Therefore, based on lanthanum modified bentonite clay (Phoslock®) and drinking water treatment residues (DWTR), the effect of P inactivating materials on sediment resuspension and settlement were comprehensively investigated to assess the variations in particulate P pollution from sediment. Results showed that both materials could effectively control soluble P pollution from sediment, while both had limited effect on the supplement of particulate P to overlying water. The reason may be that hydrodynamic disturbance was the key factor regulating sediment resuspension and settlement. The disturbance induced the resuspension of different sized sediments, especially <8 μm fractions, while increasing disturbing intensities promoted resuspension of relatively larger sized sediments (e.g., <63 μm). Further analysis suggested that after resuspension and settlement, the efficiencies of reducing bioavailable P by Phoslock® in relatively large sized sediment fraction (e.g., <63 μm) were substantially less than those in relatively small sized sediment (<8 μm). Although the reducing efficacies of DWTR had limited changes in different sized sediments, the remaining bioavailable P were clearly higher in smaller sized sediments with DWTR. The different performances on bioavailable P reduction mainly resulted from the distributions of materials and original P in different sized sediments. These findings indicated the potential supplement of particulate P for algal growth during resuspension and settlement of sediments amended by P inactivating materials. Overall, understanding the sediment P bioavailability and hydraulic properties at different sizes and the lake hydrodynamic conditions is essential to develop appropriate methods to control lake internal P pollution. Highlights: Phoslock® and water treatment residue had limited effect on particulate-P loading. Phoslock® is more feasible to reduce bioavalible P in <8 μm fraction of sediment. The residue to reduce bioavalible P in different sized sediments was similar. Sediment particulate-P required more attention for lake eutrophication control.